2010
DOI: 10.1111/j.1469-7610.2009.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance variability, impulsivity errors and the impact of incentives as gender‐independent endophenotypes for ADHD

Abstract: Background-Attention-deficit hyperactivity disorder (ADHD) is one of the most common and highly heritable child psychiatric disorders. There is strong evidence that children with ADHD show slower and more variable responses in tasks such as Go/Nogo tapping aspects of executive functions like sustained attention and response control which may be modulated by motivational factors and/or state-regulation processes. The aim of this study was (1) to determine if these executive functions may constitute an endopheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 51 publications
14
117
2
4
Order By: Relevance
“…It is important to underline that the haemodynamic changes in the dorsal ACC following the RCT training were the only which were demonstrated by a significant ANOVA interaction Group x Time. As the response variability has been discussed as a key neuropsychological abnormality underlying other neuropsychological and clinical deficits in ADHD (Sergeant et al 2002;Uebel et al 2010), it seems likely that the optimization of activity in structures responsible for performance monitoring following the RCT training causes clinical improvement in ADHD symptoms, as observed in this study.…”
Section: Effect Of Response Cost and Token Training Programmentioning
confidence: 76%
See 1 more Smart Citation
“…It is important to underline that the haemodynamic changes in the dorsal ACC following the RCT training were the only which were demonstrated by a significant ANOVA interaction Group x Time. As the response variability has been discussed as a key neuropsychological abnormality underlying other neuropsychological and clinical deficits in ADHD (Sergeant et al 2002;Uebel et al 2010), it seems likely that the optimization of activity in structures responsible for performance monitoring following the RCT training causes clinical improvement in ADHD symptoms, as observed in this study.…”
Section: Effect Of Response Cost and Token Training Programmentioning
confidence: 76%
“…Because impaired executive functioning, particular inhibitory deficits, were described as a key neuropsychological feature of ADHD (Barkley 1997;Sergeant et al 2002;Willcutt et al 2005), the study focused on the effect of the training on neuronal networks responsible for impulse control and behavioral inhibition. Using a classical Go/Nogo paradigm, a number of studies has revealed that patients with ADHD demonstrate significantly more omission errors and false alarms, are characterized by slower reaction time and higher performance variability compared to healthy controls (Castellanos et al 2005;Crosbie et al 2008;Desman et al 2008;Uebel et al 2010;Vaurio et al 2009;Wodka et al 2007). In neuroimaging studies, the lower performance of patients with ADHD in Go/No-go tasks has been associated with significantly lower activation in the anterior cingulated cortex (ACC), dorsolateral prefrontal cortex (DLPFC), caudate nuclei, and the parietal and somatosensory cortex (Booth et al 2005;Dillo et al 2010;Durston et al 2006;Epstein 2009;Smith et al 2006;Solanto et al 2009;Tamm et al 2004;Vaidya et al 1998).…”
mentioning
confidence: 99%
“…It will be worthwhile to examine MAOB and evaluate the gene-gene interaction between MAOA and MAOB in further research given the important role of MAOB in the metabolism of DA. In recent years, endophenotypes have attracted attention in genetic studies of ADHD [Doyle et al, 2005a;Doyle et al, 2005b;Rommelse et al, 2008b;Rommelse et al, 2008c;Rommelse et al, 2009;Uebel et al, 2010]. Increased penetrance of the endophenotype compared to the phenotype proper may help us to find candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Most prevalent is a clinical impairment of the combined type (around 5%: Polanczyk et al 2007). A potential endophenotype of the disorder is the variability of expression of these symptoms and of the responses on neuropsychological tests in the laboratory (Castellanos and Tannock 2002;Klein et al 2006;Kuntsi et al 2005;Uebel et al 2010). Russell et al (2006) proposed that an altered aspect of the metabolic activity of glia may underlie this variability.…”
Section: Adhdmentioning
confidence: 97%